2016
DOI: 10.12657/folmal.024.017
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Bythinella Moquin-Tandon, 1855 (Caenogastropoda: Truncatelloidea) from Naxos Island, Greece

Abstract: A new species of Bythinella: B. walensae is described from Aria spring at Naxos Island, Greece. Cytochrome oxidase subunit I (COI) sequences of mtDNA, as well as internal transcribed spacer (ITS-1) of nuclear ribosomal DNA indicate distinctness of B. walensae. The shell, female reproductive organs and penis are described. The most characteristic of this species are: slender shell, narrow aperture, J-shaped bursa coupled with bulky and spherical receptaculum, and the length ratio of penis arms. Simple anatomy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Isimerope (Radea et al 2013), and seven new locally endemic species i.e. Radomaniola feheri Georgiev, 2013 (Georgiev 2013), Daphniola magdalenae Falniowski, 2015, Iglica hellenica Falniowski, 2015 (Falniowski and Sarbu 2015), Pseudamnicola ianthe Radea & Parmakelis, 2016, Pseudamnicola ilione Radea & Parmakelis, 2016 (Radea et al 2016), Pseudamnicola magdalenae Falniowski, 2016 (Falniowski 2016a), and Bythinella walensae Falniowski, 2016 (Falniowski 2016b) were described from Greece. The introduction of one more new locally endemic genus provides clues about the richness and the high endemicity of Greek freshwater bodies, which support some of the most biodiverse and heavily threatened ecosystems of the Mediterranean Basin Biodiversity Hotspot (Szarowska and Falniowski 2004, Darwall et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Isimerope (Radea et al 2013), and seven new locally endemic species i.e. Radomaniola feheri Georgiev, 2013 (Georgiev 2013), Daphniola magdalenae Falniowski, 2015, Iglica hellenica Falniowski, 2015 (Falniowski and Sarbu 2015), Pseudamnicola ianthe Radea & Parmakelis, 2016, Pseudamnicola ilione Radea & Parmakelis, 2016 (Radea et al 2016), Pseudamnicola magdalenae Falniowski, 2016 (Falniowski 2016a), and Bythinella walensae Falniowski, 2016 (Falniowski 2016b) were described from Greece. The introduction of one more new locally endemic genus provides clues about the richness and the high endemicity of Greek freshwater bodies, which support some of the most biodiverse and heavily threatened ecosystems of the Mediterranean Basin Biodiversity Hotspot (Szarowska and Falniowski 2004, Darwall et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Schütt (1980) in his paper on Greek hydrobiid snails stated that entire Greece, except the islands of Kos and Crete, was inhabited only by B. charpentieri Roth, 1855. More recently, Falniowski & Szarowska (2011) by using molecular genetic studies demonstrated that the Greek fauna of Bythinella is much more diverse, which has been confirmed by description of a large number of species of the latter genus during the last decade (e.g., Reischütz and Fischer 2008;Falniowski et al 2016;Glöer and Hirschfelder 2019;Glöer and Hirschfelder 2020;Glöer and Reuselaars 2020a,b,c;Georgiev and Glöer 2020). To date, 23 species of the genus Bythinella have previously been described from Greece.…”
Section: Introductionmentioning
confidence: 87%
“…All other species else known from Greece are considered to be endemics on single islands (Schütt 1980, Reischütz 1988, Bank 2006, Falniowski et al 2016): B. cabirius (Reischütz, 1988) from Samothraki Island, Bythinella cretensis Schütt, 1980from Crete, B. kosensis Schütt, 1980, from the island of Kos, and Bythinella walensae Falniowski, Hofman & Rysiewska 2016) from Naxos.…”
Section: Greecementioning
confidence: 99%